The therapeutic effects of ginger extract on gastrointestinal disorders to adults - Rara Poetri Claudya; Helga Audelia Sugiaman; Salsabil Inas Labiba; Margaretha Pramesthi Utari; Deni Gunawan (Science Midwifery, 2023)
Ginger (Zingiber officinale Roscoe) which belongs to the Zingiberaceae and the genus Zingiber families, has active ingredients, such as phenolic compounds and terpenes. Some researchers conducted clinical trials to scientifically assess the effectiveness of ginger as an adjunct therapy as a complementary or alternative drug in several diseases, especially gastrointestinal diseases. This study aims to determine ginger extracts' therapeutic effects on adults' gastrointestinal disorders. The research method used descriptive qualitative through the Literature Review (LR) approach. The data source used a secondary source. Data analysis technique selects literature based on title, year, and indexed articles, then reviews articles that match the subject matter. the articles from those journals are compared to find the differences and similarities. The ginger extracts therapeutic effects are obtained in that these extracts are able to relieve nausea and vomiting due to chemotherapy by suppressing the activation of 5-HT receptors in enteric neurons. In addition, ginger relieves nausea caused by antituberculosis drugs and antiretroviral therapy. Ginger extract and its constituents also have chemopreventive and antineoplastic properties in gastric cancer.